Development of a graphical user interface for step detection program - Aung, Moh Moh (2017)
There is the previous version of Graphical User Interface for the data analysis from C program. However, little was done on functionalities and the user’s perspective in using the application. The overall existing user interface is dull: simple layout containing basic functionalities. The primary objective of this project is to continue the development of graphical user interface, and concurrently to transform the look, so that an advanced data analysis can be done seamlessly with better visualizations.